ANALISIS KUALITAS AIR IRIGASI DENGAN METODE STORET DAN METODE INDEKS PENCEMARAN (IP) PADA MONITORING SYSTEM BERBASIS IOT - Raco, Brigitha; Singgeta, Ryan Laksmana (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The degradation of water quality, a result of various human activities and climate change, poses a significant threat to agricultural productivity and food security. The complex process of testing water quality for irrigation, typically surface water, involves multiple stages and laboratory testing. This research, crucial in the current context, aims to determine water quality in irrigation using IoT-based testing, as PP. RI No. 82 tahun 2001. The use of IoT-based testing simplifies the water quality testing process. The water quality methods employed in this study are the STORET Water Quality Method and the Pollution Index Method (IP). The research focuses on the water quality in Tara Tara Village, West Tomohon District, Tomohon City, North Sulawesi. The initial research stage was to design a monitoring device with three sensors determining water quality: water temperature, TDS, and pH. Sensors are connected and integrated with the ESP32 Microcontroller. The value output can be accessed using the internet on the ThingSpeak Application. The results of the STORET method show that in class II and class III, there are pH parameters that do not meet the quality standards at the minimum value, so they get a value of -1, which classifies class II and class III as lightly polluted. However, for class IV, it shows that it is not polluted. The IP method results obtained for class II and III were 0.430, and for class IV were 0.422, with the category of meeting water quality standards. Keywords: IoT, Irrigation, Pollutant Index Method, STORET Method, Water Quality.